LEGAL PROTECTION FOR STUDENTS AS VICTIMS OF BULLYING : (CASE STUDY AT SD MEKAR REGENCY, CIREBON) - Rifqi Muhammad Zidan; Irma Maulida (Fakultas Hukum Universitas Swadaya Gunung Jati, 2027)
Background. Bullying in elementary schools remains a significant challenge that threatens children's rights, psychological well-being, and educational development. Aims. This study examines the implementation of legal protection for students who are victims of bullying at SD Mekar, Cirebon Regency, and identifies the challenges encountered in its implementation. Methods. An empirical legal research design was employed using empirical and psychological approaches. Primary data were collected through interviews with officials from the Cirebon Regency Education Office, school principals, teachers, and parents, while secondary data were obtained from legislation, legal literature, and relevant scholarly publications. Result. The findings reveal that legal protection has been implemented through both preventive and repressive measures. Preventive strategies include character education, teacher supervision, religious and moral development activities, anti-bullying awareness, and collaboration between schools and parents. Repressive measures involve receiving and investigating complaints, mediation, psychological support for victims, behavioral guidance for perpetrators, and coordination with relevant authorities, including the Education Office. These measures are grounded in Article 28B(2) of the 1945 Constitution of the Republic of Indonesia, Law No. 35 of 2014 on Child Protection, Law No. 20 of 2003 on the National Education System, and related educational regulations. Conclusion. The study concludes that effective legal protection requires stronger collaboration among schools, families, government agencies, and the wider community to foster a safe, inclusive, and child-friendly educational environment while strengthening preventive and responsive mechanisms against bullying. Implication.